PREVALENCE OF GASTROINTESTINAL HELMINTHS AMONG SLAUGHTERED CATTLE AT JALINGO ABATTOIR, TARABA STATE, NIGERIA - Jibrin, N.; Aliyara, Y.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
A cross sectional study was conducted from October 2024 to January2025, on 400 cattle at Jalingo modern abattoir, Taraba State Nigeria, based on post mortem examination on prevalence of gastrointestinal helminths and heamoparasite among slaughtered cattle’s at Jalingo abattoir. A total of 400 cattle were examined and, the total number of infected was126 and the overall prevalence rate of 31.5% from 1.White Fulani, 2.Adamawa Gudali, 3.Red bororo and 4.Sokoto Gudali breeds. The highest prevalence rate (35.96%) was recorded in White fulani, followed by Sokoto gudali (20%) then 15.79%, 6.98% for Red bororo and Adamawa Gudali, respectively. Prevalence rate for the males was 22.62% and 33.86% for females whereas 33.23%, 29.58% and 22.72% were recorded for age group 1-2, 3-4 and >5 years respectively. The result showed no significant difference (P>0.05) on prevalence of infection between breed, sex and age. Also according to sex, out of 316 female examined 107(33.86%) were infected and out of 84 male examined 19(22.62%) were infected. Statistically, there was no significant difference (P>0.05) exist among male and female. According to the age out of 400 cattle examined 126 (31.5%) were infected. There was no statistical significant (P>0.05) between age group. Result showed gastrointestinal helminths is prevalence in Jalingo modern abattoir, hence public health significance of gastrointestinal helminths in cattle affecting humans and animals, most of these parasites are zoonotic, condemnation of carcasses there is need to embark on control and eradication of affected cattle and the general public should be enlightening on the helminths and meat inspection/sanitary condition should be improved.